Synthesis of Silver Nanoparticles of Corn Silk Agrowaste and Their Bioactivities - Fuloria, S.; Hong, O.J.; Kim, C.B.; Ting, B.Y.S.; Karupiah, S.; Paliwal, N.; Kumari, U.; Sathasivam, K.; Vetriselvan, S.; Fuloria, N.K. (Asian Journal of Chemistry, 2020)
Present study was intended to synthesize silver nanoparticles (AgNPs) using corn silk aqueous extract (CSAE) and evaluate for antimicrobial and antiurolithiatic potential. The aqueous decoction of corn silk offered light yellow CSAE. Treatment of AgNO3 with CSAE offered AgNPs with absorbance 430 nm. Optimization study established 5 mM silver nitrate, 2.5:7.5 extract to AgNO3 ratio, pH 8, and 24 h time as parametric requirement for synthesis of AgNPs using CSAE. Stability study supported the AgNPs stability based on retention of SPR signal between 428 to 450 nm. The synthesis of AgNPs was confirmed on broad and shifted FTIR bands; XRD signals at 2θ values of 32.27º, 40.72º, 46.20º, 65.69º, 69.31º and 76.49º indexed to 111, 200, 220 and 311 planes, respectively; particle size range from 22.05-36.69 nm in FESEM; and elemental silver content of 62.17% as per EDX spectrum. The synthesized AgNPs exhibited high antibacterial and antiurolithiatic potential. Present study recommends that synthesis of AgNPs using CSAE is a facile and eco-friendly method.